Pseudonocardia Symbionts of Fungus-Growing Ants and the Evolution of Defensive Secondary Metabolism - Goldstein, Sarah L.; Klassen, Jonathan L. (Frontiers in Microbiology, 2020)
Actinobacteria belonging to the genus Pseudonocardia have evolved a close relationship with multiple species of fungus-growing ants, where these bacteria produce diverse secondary metabolites that protect the ants and their fungal mutualists from disease. Recent research has charted the phylogenetic diversity of this symbiosis, revealing multiple instances where the ants and Pseudonocardia have formed stable relationships in which these bacteria are housed on specific regions of the ant’s cuticle. Parallel chemical and genomic analyses have also revealed that symbiotic Pseudonocardia produce diverse secondary metabolites with antifungal and antibacterial bioactivities, and highlighted the importance of plasmid recombination and horizontal gene transfer for maintaining these symbiotic traits. Here, we propose a multi-level model for the evolution of Pseudonocardia and their secondary metabolites that includes symbiont transmission within and between ant colonies, and the potentially independent movement and diversification of their secondary metabolite biosynthetic genes. Because of their well-studied ecology and experimental tractability, Pseudonocardia symbionts of fungus-growing ants are an especially useful model system to understand the evolution of secondary metabolites, and also comprise a significant source of novel antibiotic and antifungal agents.